Monophasic synovial sarcoma of the ethmoid sinus - Chowdhary, Stuti; Sekar, Raghul; Saxena, Sunil Kumar; Srinivas, Bheemanathi Hanuman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Sino-nasal synovial sarcomas are rare mesenchymal tumours, most arising primarily from the paranasal sinuses. Very few have been described with an extension to the nasal cavity. Due to a range of non-specific symptoms and local aggressiveness, diagnosis tends to be confusing. Here we describe a case of a primary sino-nasal monophasic synovial sarcoma, diagnosed by histopathology and treated by excision and adjuvant radiation therapy. On follow-up, the patient had minimal residual disease and was further offered revision surgery and chemotherapy. She declined surgery and received chemotherapy, and remains symptom-free to date. A wide range of diagnoses should be considered for nasal masses since all tissue types coexist in this region.